Pengaruh Tinta Cumi-Cumi (Loligo sp.) Terhadap Kualitas dan Kuantitas Spermatozoa Mencit (Mus musculus L.) yang Diinduksi D-Galaktosa - Safitri, Dewi Restika Ayu; Sutyarso, Sutyarso; Busman, Hendri; Nurcahyani, Nuning (Undiksha, 2023)
Increased levels of free radicals in the body are thought to trigger oxidative stress and cause aging. Biologists state that aging is one of the causes of infertility in men. Squid ink is known to have high antioxidant activity so that it can be used as an alternative treatment. Therefore, this study was conducted with the aim of knowing the effect of inking squid on the quality and quantity of male individual spermatozoa, which included sperm count, motility, and viability of the spermatozoa of mice experiencing oxidative stress due to D-Galactose induction. This research was conducted experimentally in December 2022 – March 2023 where 24 male mice were divided into 4 groups, namely K, K- (D-Gal 150 mg/kgBB), P1 (D-Gal 150 mg/kgBB + squid ink 40 mL/kgBB), and P2 (D-Gal 150 mg/kgBB + squid ink 100 mL/kgBB). The results showed that squid ink was able to increase the quality and quantity (sperm count, motility, and viability) of mice spermatozoa which had previously decreased due to D-Galactose induction, where the best results for each parameter were shown by P2.